In vivo and in vitro anti-inflammatory effects of Zao-Jiao-Ci (the spine of Gleditsia sinensis Lam.) aqueous extract and its mechanisms of action. (4th November 2016) - Li, Kai Kai; Zhou, Xuelin; Wong, Hing Lok; Ng, Chun Fai; Fu, Wei Ming; Leung, Ping Chung; Peng, Guiyuan; Ko, Chun Hay
Abstract: Ethnopharmacological relevance: Zao-Jiao-Ci (ZJC), as the spine of Chinese Honey locust ( Gleditsia sinensis Lam.), is traditionally used as Chinese medicine to reduce inflammation. Aim of the study: The present study aimed to investigate an anti-inflammatory effect of ZJC aqueous extract both in vitro and in vivo, as well as its underlying mechanisms. Materials and methods: Anti-inflammatory effect of ZJC aqueous extract was evaluated by using carrageenan-induced paw edema in rats. In addition, the inhibitory effects of ZJC on nitric oxide production, intracellular reactive oxygen species production, pro-inflammatory mediator expression and prostaglandin E2 (PGE2 ) production were determined by using LPS-activated RAW 264.7 cells. The anti-oxidant activity of ZJC was assessed using 2, 2′-azino-bis-3-ethylbenzthiazoline-6-sulfonic acid assay. Results: ZJC aqueous extract showed significant suppressive effect on paw edema in rats at 100 mg/kg. Moreover, ZJC aqueous extract decreased the expression of cyclooxygenase (COX)-2 and significantly decreased the PGE2, tumor necrosis factor-α, interleukin (IL)-1β and IL-6 production in LPS-activated macrophages in dose-dependent manners. ZJC aqueous extract inhibited the mRNA expression of these inflammatory cytokines as well. Furthermore, ZJC aqueous extract was found as an anti-oxidant and could inhibit ROS production in the LPS-induced cells. Conclusions: These findings show the potential of ZJC aqueous extract as a naturally occurring COX-2 inhibitor to reduce inflammation. Graphical abstract: